Atomistically-informed crystal plasticity in MgO polycrystals under pressure. (July 2016) - Amodeo, J.; Dancette, S.; Delannay, L.
Abstract: This paper addresses multi-scale modeling of a special kind of pressure-dependent plasticity. In MgO, which is a major constituent of the Earth's lower mantle, the relative activity of the 1 2 〈 110 〉 { 110 } and 1 2 〈 110 〉 { 100 } slip modes depends on the level of hydrostatic pressure. The influence of pressure on both the dislocation core structures and the collective behavior of dislocations may be computed based on atomistic modeling and dislocation dynamics simulations. In the present study, results from such lower-scale simulations are used to determine the parameters of a crystal plasticity model that is suitable in order to probe the large-scale mechanical response of MgO polycrystals at pressures up to 100 GPa. The model is assessed based on experimental compression tests performed at different pressure levels. It turns out that the responses of single crystals and polycrystals are fundamentally different. Moreover, due to the large anisotropy of individual crystals, the outcome of polycrystalline simulations is found to depend strongly on the modeling assumption made about grain interactions. Crystal plasticity based finite element modeling provides the best predictions of the texture development when comparing to recent high pressure experiments. Highlights: An atomistically-informed crystal plasticity model is developed to study the deformation of MgO under pressure. In single crystals, the CP model predicts that {110} and {100} slip modes dominate, respectively, below and beyond 30 GPa. In polycrystals, the predictions of the CP law vary with the assumptions formulated about adjacent grains interactions. In polycrystals, both {110} and {100} slip modes are activated together whatever the pressure range. CPFEM reproduces experimental textures as well as the larger flow stress of polycrystals as compared to single crystals.